Intracystic gastrointestinal stromal tumor developed in the round ligament of the liver - Naoki Kataoka; Shoji Oura; Akito Furuta (Radiology Case Reports, 2024)
A 44-year-old woman was referred to our hospital for the examination and treatment of a presumed gallbladder tumor. Both ultrasound and computed tomography showed an intracystic tumor but failed to point out the discontinuity between the cystic lesion and the gallbladder. Magnetic resonance imaging, however, could clearly depict the presumed intracystic tumor and the discontinuity between the gallbladder and the target lesion. Both contents of the gallbladder and the cystic lesion showed hypo and hyper intense patterns, though both with slightly different intensities, on T1- and T2-weighted images, respectively. Under the preoperative diagnosis of early gallbladder cancer despite these image findings, laparoscopic cholecystectomy was attempted to the patient. Laparoscopic observation, however, revealed that the target lesion was not continuous with the gallbladder and was located in the round ligament of the liver. Intraoperative findings led us to do cholecystectomy and resection of the adjacent cystic tumor. The intracystic tumor was 3 cm in size and had minute solid component inside the cyst wall. Pathological study of the presumed gallbladder cancer showed epithelioid cells and spindle cells growing in sheet like and storiform fashions, respectively. Cystic walls mainly consisted of hypo cellular fibrous components. Immunohistochemical staining of the tumor was positive for CD117 and negative both for desmin and S100, leading to the diagnosis of gastrointestinal stromal tumor. MIB-1 labelling index of the gastrointestinal stromal tumor was 8%. The patient recovered uneventfully and has been well without any recurrences for 3 months.